Maladaptive stress-coping behavior in CX3CR1-deficient mice: Impact of adolescent stress and alcohol exposure on neuroimmune responses and inflammation - Medina-Vera, Dina; Martín-Chaves, Laura; Sánchez-Marín, Laura; Díaz-Ottaviano, María; Gavito, Ana L.; Popova, Olga; Sánchez-Quintero, María José; Rodríguez Capitán, Jorge; Rodriguez-de-Fonseca, Fernando; Jiménez-Navarro, Manuel Francisco; Serrano, Antonia; Pavón-Morón, Francisco Javier (Elsevier, 2025)
The CX3CL1/CX3CR1 chemokine axis regulates synaptic pruning, plasticity, and stress-related behaviors, influencing resilience or vulnerability to psychiatric disorders. Adolescence, a critical period for neuroimmune development, increases susceptibility to stressors. This study investigated how adolescent restraint stress and alcohol exposure affect stress-coping behavior, neuroimmune signaling, and systemic inflammation in adult wild-type (WT) and CX3CR1 knock-out (KO) mice. Eighty-one male and female WT and KO mice were assigned to control (non-stressed, saline-treated), stress (stressed, saline-treated), alcohol (non-stressed, alcohol-treated), and stress + alcohol (stressed, alcohol-treated) groups. Behavioral responses were evaluated using the tail suspension test. Hypothalamic gene expression of CX3CL1/CX3CR1, corticotropin-releasing hormone (CRH), and neuropeptide Y (NPY) systems was analyzed alongside plasma corticosterone, adrenocorticotropic hormone (ACTH), CX3CL1, and inflammatory mediators. Adolescent stress—but not alcohol—increased plasma CX3CL1 levels, which inversely correlated with immobility time in WT mice. KO mice displayed higher baseline immobility than WT mice, whereas stress and/or alcohol paradoxically reduced immobility. These behavioral effects were reproduced by pharmacological inhibition of CX3CR1. Additionally, KO mice showed disrupted hypothalamic expression of multiple genes in the CRH pathway and Npy1r, attenuated corticosterone responses to stress, and abolished ACTH–corticosterone correlation, suggesting HPA axis dysregulation. KO mice also exhibited exacerbated inflammatory responses to stress and alcohol, including elevated IL-17A/F, IL-11, and IFN-β1 levels.
Keywords: Ratones de laboratorio - Efectos del estrés; Alcohol - Efectos fisiológicos; Citoquinas; Neurofarmacología; Alcohol; Stress; Fractalkine; Inflammation; Stress-coping behavior; Tail suspension